2014
DOI: 10.1111/hsc.12099
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and social support of older people living alone in a county of Shanghai, China

Abstract: China has an ageing population with the number of older people living alone increasing. Living alone may increase the risk of loneliness of older people, especially for those in China where collectivism and filial piety are emphasised. Social support may fill the need for social contacts, thereby alleviating loneliness. However, little is known about loneliness and social support of older people living alone in China. This study investigated loneliness and social support of older people living alone, by conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 40 publications
6
45
0
4
Order By: Relevance
“…Our study replicated previous findings that marital relationship plays a protective role against feelings of loneliness (Chen et al, 2014;Gow et al, 2013;Perissinotto, Stijacic Cenzer, & Covinsky, 2012). We found that married participants, including those remarried and cohabited, reported lower levels of perceived loneliness when compared with their non-married counterparts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study replicated previous findings that marital relationship plays a protective role against feelings of loneliness (Chen et al, 2014;Gow et al, 2013;Perissinotto, Stijacic Cenzer, & Covinsky, 2012). We found that married participants, including those remarried and cohabited, reported lower levels of perceived loneliness when compared with their non-married counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…Third, we aimed to identify some demographic correlates of loneliness such that the information would be useful for health care professionals or policy makers to address the issue of loneliness in older adults. Previous studies suggest that being female, unmarried, having lower levels of education and living alone were associated with higher levels of loneliness (Chen, Hicks, & While, 2014). The degree to which these demographic variables correlated with loneliness in community-dwelling older adults would be examined in the current study.…”
Section: Introductionmentioning
confidence: 96%
“…; Kravdal ; Steptoe et al. ; Umberson and Montez ); to the fact that living alone tends to reduce satisfaction with life and the perceived quality of life in old age (Jakobsson, Hallberg, and Westergren , Gaymou and Springer 2012); and the fact that living alone lowers levels of social and familial support at older ages (Thompson and Krause , Chen, Hicks, and While ). Little is known about the effects of living arrangements on health outcomes, although poorer health and higher death rates can be expected from older people living alone (Koskinen et al.…”
Section: Future Trends and Relevance For Policymentioning
confidence: 99%
“…Loneliness has been shown to be influenced by socio‐demographic characteristics such as gender, household income, household living arrangements and health status (Pikhartova, Bowling, & Victor, ). Chen, Hicks, and While () and Hazer and Boylu () emphasised that people of advanced age who have a lower level of education, have a lower economic status and live in a rural area are at higher risk of loneliness and should therefore be given a higher priority for preventive interventions.…”
Section: Introductionmentioning
confidence: 99%